(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article provides a comprehensive analysis of the socio-psychological mechanisms of personal responsibility formation as an integrative quality that determines an individual’s maturity, social adaptation, and moral resilience. Based on a synthesis of modern scientific approaches, key psychological and sociocultural factors determining the development of responsible behavior are identified and systematized. Particular attention is paid to the role of the family, the educational system, internal motivation, and self-regulation processes as fundamental conditions for the formation of a responsible attitude towards oneself and society. The author’s model of responsibility as a dynamic formation arising at the intersection of the internalization of social norms and the development of personal autonomy is substantiated. The practical significance of the study lies in the possibility of developing corrective and educational programs based on its findings.